LEGAL PROTECTION OF PATIENT MEDICAL RECORD DATA IN TELEMEDICINE HEALTH SERVICES BASED ON LAW NUMBER 17 OF 2023 CONCERNING HEALTH AND LAW NUMBER 27 OF 2022 CONCERNING PERSONAL DATA PROTECTION - Andreas Henfri Situngkir; Rahmayanti (PT. Radja Intercontinental Publishing, 2026)
Law Number 27 of 2022 concerning Personal Data Protection, Personal Data is a fundamental right that must be protected in every healthcare service interaction and in Law Number 17 of 2023 concerning Health is the legal basis for regulating Health in addition to that until now legal clarity regarding licensing and permits that regulate Telemedicine healthcare services is also regulated in Minister of Health Regulation Number 20 of 2019 which stipulates that medical personnel and healthcare facilities must obtain a license to carry out telemedicine. In the practice of online healthcare consultations, medical data protection is highly dependent on the technological system used by the service provider. Digital healthcare platforms generally rely on website-based databases or applications connected to the internet network. Legal protection in Telemedicine services must be able to protect the dignity of recipients and healthcare providers in the implementation of Telemedicine so that their rights and obligations can be fulfilled in line with human rights inherent from birth.